MEMAHAMI KONSEP STRATEGI PEMBELAJARAN BERBASIS KONSEP DAN PEMECAHAN MASALAH - Vera Nur Azizah; Arif Riki Wardana; Nabila Safira; Nisrina Widha Hapsari; Nurhaswinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the concept of concept-based and problem-solving learning strategies and their role in improving the quality of the learning process. This study employed a qualitative approach with library research. Data were obtained from various sources, such as books, scientific journals, research articles, and academic documents relevant to the research topic. Data collection was conducted through documentation studies, reviewing various references related to concept-based and problem-solving learning strategies. Data analysis was conducted using qualitative descriptive methods, reviewing, comparing, and interpreting various theories and previous research findings. The results indicate that concept-based learning strategies can help students understand material more deeply through understanding the relationships between concepts. Meanwhile, problem-solving learning strategies can improve students' critical and analytical thinking skills, as well as their ability to solve various problems. Several studies analyzed also demonstrated improvements in learning outcomes, learning activities, and student participation in the learning process after implementing these two strategies. Thus, concept-based and problem-solving learning strategies can be effective learning approaches to improve the quality of the learning process and develop students' higher-order thinking skills.